Performance and Priorities: A Cross-sectional Study of Local Health Department Approaches to Essential Public Health Services. (January 2020) - Wallace, Megan; Sharfstein, Joshua; Lessler, Justin
Objectives: Despite a push for increased local public health capacity, no clear baseline for performance of local health departments (LHDs) exists. The objectives of this study were to quantify the self-reported performance of LHDs on the 10 Essential Public Health Services (EPHSs) and describe the relationships between performance and characteristics of LHDs. Methods: We used data on 2000 LHDs from the 2013 National Profile of Local Health Departments survey to develop principal components analysis–based scores to evaluate each LHD on the performance of EPHSs. Scores ranged from 0 to 100. LHDs that performed no activities within an EPHS had a score of 0, and LHDs that performed all activities within an EPHS had a score of 100. We explored the relationships between EPHS scores and LHD characteristics by using multivariate linear regression and cluster analysis. Results: Performance scores varied greatly by LHDs and EPHSs; however, LHDs typically scored <50, indicating that they performed fewer than half of the activities evaluated. LHDs that served larger populations (vs smaller populations) and LHDs that had higher per-capita funding (vs lower per-capita funding) had higher EPHS scores. We identified 6 EPHS performance score–based LHD clusters, which suggests similarities in which EPHSs LHDs focused on. Conclusions: Our results suggest weaknesses in many LHDs' fulfillment of the EPHSs, particularly in low-population and low-funding settings. LHDs should be given the resources to increase capacity and ensure the EPHSs are met in communities.